Assessment of hand bone loss in rheumatoid arthritis by high-resolution peripheral quantitative CT. Issue 9 (4th June 2010) - Fouque-Aubert, Anne; Boutroy, Stéphanie; Marotte, Hubert; Vilayphiou, Nicolas; Bacchetta, Justine; Miossec, Pierre; Delmas, Pierre Dominique; Chapurlat, Roland D
Abstract : Objectives: A new high-resolution peripheral quantitative CT (HR-pQCT) system allows for in vivo assessment of bone microarchitecture and volumetric bone mineral density (vBMD) with an 82 µm isotropic resolution. With this device, the microarchitecture impairment was evaluated in patients with rheumatoid arthritis (RA) in comparison with healthy controls and measured the erosion volume at metacarpal heads (MCPs). Methods: In this cross-sectional study, the reproducibility was first assessed by 3 HR-pQCT exams with repositioning in 14 patients with late RA and 14 healthy subjects. Then, HR-pQCT parameters were measured in a group of 93 patients with RA and 31 healthy controls. Two RA subgroups were distinguished: early RA (disease duration ≤2 years) (n=36) and late RA (n=57) and compared them to healthy controls. Results: The precision of the HR-pQCT volumetric measurements as assessed with coefficient of variation ranged from 0.7% to 1.8% in patients with late RA and from 0.6% to 1.4% in healthy subjects at MCPs. Total and trabecular vBMD and trabecular thickness were significantly decreased in patients with RA compared to healthy subjects and were significantly correlated to disease activity. The erosion volume was highly correlated to a semiquantitative assessment using the Outcome Measures in Rheumatoid Arthritis Clinical Trials (OMERACT) scoring system applied to the HR-pQCT slices. Conclusions: This study demonstrated the good reproducibility of the HR-pQCT volumetric measurements at MCPs and confirmed the involvement of trabecular compartment in periarticular osteopoenia. Thus, HR-pQCT appears interesting to simultaneously assess differences in bone volumetric density, microarchitecture and erosions.